Proceedings of the 33rd Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems 2015
DOI: 10.1145/2702613.2732852
|View full text |Cite
|
Sign up to set email alerts
|

"It Was Sad But Still Good"

Abstract: Players have increasingly become interested in emotional game experiences beyond simple "fun". Although previous research has identified several gratifications of fun experiences, still little is known about whether and what gratifications players derive from emotionally moving game experiences. Interviews with 12 Japanese and Western players revealed several gratifications, such as liking to experience strong emotions, whereas other players did not enjoy being emotionally moved, but appreciated that the emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Researchers such as Bopp et al [8], [20] chose to focus on negatively valenced emotions, which, while being present in the player experience, were mostly unresearched. This is due to a prevalent belief of negative emotions being at odds with the focus on positive affect and enjoyment that video games should provide.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers such as Bopp et al [8], [20] chose to focus on negatively valenced emotions, which, while being present in the player experience, were mostly unresearched. This is due to a prevalent belief of negative emotions being at odds with the focus on positive affect and enjoyment that video games should provide.…”
Section: Related Workmentioning
confidence: 99%
“…Likewise, many games use their narrative to evoke emotions such as sadness, which is described by players in their reports of notable emotionally driven experiences [20]. This sort of emotional response is tied to relatedness, which can also present itself as a variation of loneliness, melancholy, and grief [12].…”
Section: A Negativity In Media and Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the experience could be influenced by the mechanics and narrative plot of the game it could be useful for the designers aiming to make the player feel negative emotions (see Denisova et al, 2021), which studies have shown could make the player feel satisfied after completing the game (e.g., Bopp et al, 2016) but on the other hand, make them reconsider some choices if the experience could be harmful afterwards. Lastly, research on post-game depression can be a valuable contribution to the growing number of research focusing on factors other than fun and hedonistic enjoyment from the game (e.g., Bopp et al, 2015Bopp et al, , 2016Bopp et al, , 2018Boyle et al, 2012;Daneels, Malliet et al, 2021;Elson et al, 2014;Jennet et al, 2008;Kim et al, 2015;Mekler et al, 2014Mekler et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in their research on the multiplayer survival videogame DayZ , Carter and Allison (2019) situate transgressive play in moral disengagement and argue that the traditionally ‘undesirable’ emotions experienced throughout DayZ gameplay—like guilt—are part of the appeal of the game for players. Likewise, Bopp et al (2015, 2016; Bopp et al, 2018) have explored the motivations towards experiencing uncomfortable or negative emotions from players of various digital games. They argue that “negative emotions [experienced] in games may indeed contribute to positive player experiences [overall]” (Bopp et al, 2016), which is further supported by Hopeametsä’s (2014) and Montola’s (2010) examinations of “positive negative” play experiences in live action role-playing games [LARPs].…”
Section: Introductionmentioning
confidence: 99%